Characterization of a Synaptic Vesicle Binding Motif on the Distal CaV2.2 Channel C-terminal - Gardezi, Sabiha R.; Nath, Arup R.; Li, Qi; Stanley, Elise F. (Frontiers in Cellular Neuroscience, 2016)
Neurotransmitter is released from synaptic vesicles (SVs) that are gated to fuse with the presynaptic membrane by calcium ions that enter through voltage-gated calcium channels (CaVs). There is compelling evidence that SVs associate closely with the CaVs but the molecular linking mechanisms remain poorly understood. Using a cell-free, synaptic vesicle-pull-down assay method (SV-PD) we have recently demonstrated that SVs can bind both to the intact CaV2.2 channel and also to a fusion protein comprising the distal third, C3 segment, of its long C-terminal. This site was localized to a 49 amino acid region just proximal to the C-terminal tip. To further restrict the SV binding site we generated five, 10 amino acid mimetic blocking peptides spanning this region. Of these, HQARRVPNGY effectively inhibited SV-PD and also inhibited SV recycling when cryoloaded into chick brain nerve terminals (synaptosomes). Further, SV-PD was markedly reduced using a C3 fusion protein that lacked the HQARRVPNGY sequence, C3HQless. We zeroed in on the SV binding motif within HQARRVPNGY by means of a palette of mutant blocking peptides. To our surprise, peptides that lacked the highly conserved VPNGY sequence still blocked SV-PD. However, substitution of the HQ and RR amino acids markedly reduced block. Of these, the RR pair was essential but not sufficient as the full block was not observed without H suggesting a CaV2.2 SV binding motif of HxxRR. Interestingly, CaV2.1, the other primary presynaptic calcium channel, exhibits a similar motif, RHxRR, that likely serves the same function. Bioinformatic analysis showed that variations of this binding motif, +(+)xRR (where + is a positively charged aa H or R), are conserved from lung-fish to man. Further studies will be necessary to identify the C terminal motif binding partner on the SV itself and to determine the role of this molecular interaction in synaptic transmission. We hypothesize that the distal C-terminal participates in the capture of the SVs from the cytoplasm, initiating their delivery to the active zone where additional tethering interactions secure the vesicle within range of the CaV single Ca2+ domains.